Les multiples formes actuelles de la conversion d’élevages laitiers de montagne vers la production de viande - Hélène Rapey (Revue de Géographie Alpine)
The wholesale deregulation of EU milk pricing markets set in motion by the 2003 CAP reforms has brought with it an uncertain future for the dairy sector. Tougher competition in and between highland and lowland regions raises fears of an increase in the number of French mountain dairy farms going out of production. Dairy farms’ conversion from milk to meat has been gathering pace since the 2008 dairy market crisis, yet there has been little attempt to study the concomitant changes in post-conversion farm structure and land-use practices. Here we address this gap through surveys of newly converted farms in the Massif Central. Our results show that milk-to-meat conversions are currently occurring in all kinds of trajectories (extend, hold or wind-down). Post-conversion farms show a greater reliance on grassland as a diet resource and improved forage self-sufficiency without making wholesale changes to their legacy forage systems. Farmer-cited perceptions of the changes that accompany conversion revolve around better quality of work and quality of life. The study finds that the trajectory of milk-to-meat conversion takes many forms and occurs in different territories. Taken together, the evidence advocates for greater territory-level (milk collection region) outreach and extension support to these conversions that are not just limited to less dynamic dairy-area farms ‘losing ground’.